Long-lived stau, sneutrino dark matter and right-slepton spectrum - Shankha Banerjee; Geneviève Bélanger; Avirup Ghosh; Biswarup Mukhopadhyaya (Journal of High Energy Physics, 2018)
Abstract The minimal supersymmetric (SUSY) standard model (MSSM) augmented by right chiral sneutrinos may lead to one such sneutrino serving as the lightest supersymmetric particle and a non-thermal dark matter candidate, especially if neutrinos have Dirac masses only. In such cases, if the lightest MSSM particle is a stau, the signal of SUSY at the LHC consists in stable charged tracks which are distinguishable from backgrounds through their time delay between the inner tracker and the muon chamber. We show how to determine in such scenarios the mass hierarchy between the lightest neutralino and right sleptons of the first two families. The techniques of neutralino reconstruction, developed in earlier works, are combined with the endpoint of the variable M T 2 in smuon (selectron) decays for this purpose. We show that one can thus determine the mass hierarchy for smuons (selectrons) and neutralinos up to 1 TeV, to the level of 5-10%.